Variation in the relationship between birth weight and subsequent obesity by household income - Jonas Minet Kinge (Health Economics Review, 2017)
There is evidence to suggest that high birth weight increases subsequent BMI. However, little attention has been paid to variations in this impact between population groups. This study investigates the relationship between high birth weight and subsequent obesity, and whether or not this relationship varies by household income. Data was taken from fourteen rounds of the Health Survey for England (between 2000-2014; N = 31,043) for children aged 2-16. We regressed obesity in childhood against birth weight, accounting for interactions between birth weight and household income, using sibling-fixed effects models. High birth weight was associated with increased risk of subsequent obesity. This association was significantly more pronounced in children from low-income families, compared with children from high-income families. A 1 kg increase in birth weight increased the probability of obesity by 7% in the lowest income tertile and 4% in the highest income tertile. This suggests that early socioeconomic deprivation compound the effect of high birth weight on obesity.
Keywords: 330; Birth weight; Obesity; Body mass index; Socioeconomic status; Sibling fixed-effects